2019
DOI: 10.3390/plants8100378
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological Plasticity and Cold Stress Adaptation in Himalayan Alpine Herbs: Bistorta affinis and Sibbaldia procumbens

Abstract: Plants have evolved several metabolic pathways as a response to environmental stressors such as low temperatures. In this perspective, it is paramount to highlight physiological mechanisms of plant responses to altitudinal gradients as a proxy to evaluate changing environments. Here, we aimed to determine the impact of elevation on the physiological attributes of two plant species along an altitudinal gradient. Our hypothesis was that the altitudinal gradient influences proline, protein, and sugar contents, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Indeed, there is no order of importance of environmental variables, but studies are unanimous in showing that there is a consensus on the explanations for the variables' influences. For instance, in two recent studies we showed that the altitude-temperature relationship significantly influenced the physiological attributes of some plant species in the Northwestern Himalayan region [22,23], which can be a proxy for understanding plant adaptation to climate change. Any change in soil parameters has a significant effect on the growth of plant communities [19].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, there is no order of importance of environmental variables, but studies are unanimous in showing that there is a consensus on the explanations for the variables' influences. For instance, in two recent studies we showed that the altitude-temperature relationship significantly influenced the physiological attributes of some plant species in the Northwestern Himalayan region [22,23], which can be a proxy for understanding plant adaptation to climate change. Any change in soil parameters has a significant effect on the growth of plant communities [19].…”
Section: Plos Onementioning
confidence: 99%
“…However, despite this high endemism of species greatly influenced by various environmental gradients, such as edaphic, climatic and physiographic variables [19], these areas suffer a major impact from climate change [20,21]. Plant species present in these gradients have great adaptive power [22,23]; however, the speed with which climate change is advancing might not be sufficiently achieved by plant species adaptation in these areas, leading to a strong impact on the biodiversity of these areas [24][25][26], ultimately leading to variations in the community structure [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current field investigation was conducted in the pure Deodar forests of the Manoor valley, which is a hilly valley (Figure 1) in Pakistan's Northwestern Himalayan region [27][28][29][30], with elevations ranging from 1580.8 m to 2373.8 m. In the Himalayas, monsoon winds are the principal source of precipitation as well as the primary governing factor of erosion, topography, environment, and vegetation [31]. The valley's vegetation features Sino-Japanese characteristics [32,33].…”
Section: Study Areamentioning
confidence: 99%